2004
DOI: 10.1007/s00204-003-0532-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sensitivity of different toxicological endpoints in Caco-2 cells after cadmium chloride treatment

Abstract: The human colorectal adenocarcinoma cell line Caco-2 is a widely used in vitro model of the intestinal barrier. Cadmium chloride (CdCl(2)) is a highly toxic metal compound, ubiquitous in the biosphere, able to enter the food chain and to reach the intestinal epithelium, causing structural and functional damages. The aim of this work was to characterise cadmium toxicity in Caco-2 cells and, in particular, to compare the sensitivity of different endpoints revealing damage both on the epithelial barrier and at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In various cell models, it has been previously shown that low doses of Cd markedly increased the expression of MT1X, HMOX-1 and HSP70 [12,[39][40][41][42][43][44][45][46][47] suggesting their usefulness as biomarkers for evaluating the toxicity of Cd at low doses and the ability of the cells to respond to such stress [15]. Our results showed that apical treatment strongly induced MT1X at non cytotoxic concentrations, with only a slight induction of HMOX-1 and no effect on HSP70 expression.…”
Section: Discussionsupporting
confidence: 47%
“…In various cell models, it has been previously shown that low doses of Cd markedly increased the expression of MT1X, HMOX-1 and HSP70 [12,[39][40][41][42][43][44][45][46][47] suggesting their usefulness as biomarkers for evaluating the toxicity of Cd at low doses and the ability of the cells to respond to such stress [15]. Our results showed that apical treatment strongly induced MT1X at non cytotoxic concentrations, with only a slight induction of HMOX-1 and no effect on HSP70 expression.…”
Section: Discussionsupporting
confidence: 47%
“…In this study, we used long-term testing up to 10 lmol/l cadmium, a concentration previously shown not to be cytotoxic (Boveri et al 2004;Huynh-Delerme et al 2005). Some authors have studied the influence of a serum-free medium or a serum-supplemented medium (Finley et al 1995;Reeves et al 2001;Ranaldi et al 2003) on the cells.…”
Section: Discussionmentioning
confidence: 97%
“…Although the culture media differ, all these studies have been performed using serum-free media. To our knowledge, there is no LC 50 value published for Cd in Caco-2 cells, but from FACScan analyses with PI, an LC 50 of about 75 lM can be estimated at 24 h (Boveri et al 2004). Also a 13-fold increase in LDH leakage was measured by Blais et al (1999) following a 24-h exposure to 24 lM Cd.…”
Section: Constitutive and Acquired Resistance To CD Vary With The Difmentioning
confidence: 99%
“…Damage to intestinal epithelium integrity, including increased paracellular permeability, altered cell viability and inflammatory response, have been reported following exposure to Cd (Duizer et al 1999;Boveri et al 2004;Berzina et al 2007). Cd also favors the production of oxygen species leading to oxidative stress (Wang et al 2004), and induces stress proteins such as MT-IIa, a metal-binding protein, and the heat shock protein HSP70 (Reeves and Rossow 1996;Kiang and Tsokos 1998;Blais et al 1999).…”
Section: Introductionmentioning
confidence: 97%